Anastomosis study protected aorto-prosthetic - Servetti, Eduardo; Pardo, Hector A.; Cartazzo, José; Parodi, Hernán; Bonaba, Roberto (Cirugía del Uruguay, 1975)
The authors report an 8-dog series, in wrich they substitute a part of the infra-renal abdominal aorta by a knitted Dacron prosthesis, protecting the proximal anastomosis with a sheath of the prosthesis. The technical difficulties are discussed, and comparative histologic studies are performed of the healing process in both anastomosis. It is concluded that the sheath does not protect from immediate postoperative bleeding due to a defective suture, and that, besides an initial delay of the healing process, it does not create differences in the subsequent evolution of both anastomosis, so that it does not appear to have significance on the possible occurrence of complications.